MANAGEMENT OF TAX RISKS IN SYSTEM OF MANAGEMENT ACCOUNTING - Mаrina V. Shtiller (Статистика и экономика, 2016)
In article questions on decrease in tax risk within management accounting are considered. The main characteristics inherent in tax risk are defined behavior models of taxpayers are allocated. The author studied interrelation of tax planning and tax risk and defined its special value for decrease in tax risk.